Camera Motion Estimation based on Phase Correlation - Abdulkareem Abdulkadhem, Abdulkadhem; A. Al-Assadi, Tawfiq (International Journal of Engineering and Technology, 2018)
In this paper, we introduce a new style for a relative localization estimation and trajectory determination of a camera sensor based on a vision in GPS-denied environments. The input to the system is video film taken from a camera placed on the vehicle as forward facing camera. The output of the system is a trajectory (path) of camera movement .The proposed framework consists of many main steps, the first one extracts the FFT of two consecutive frames of video. The next step is to find the entry-wise product of frequency domain of frames. The third step is extracting the FFT inverse of entry-wise product. Next, the system finds the location of a maximum peak that represents the translation motion between two frames of video. The proposed system is faster than traditional methods that depend on spatial features and system have done without any external information of camera calibration.Â Â